Differences in the critical dynamics underlying the human and fruit-fly connectome - Géza Ódor; Gustavo Deco; Jeffrey Kelling (Physical Review Research, 2022)
Previous simulation studies on human connectomes suggested that critical dynamics emerge subcritically in the so-called Griffiths phases. Now we investigate this on the largest available brain network, the 21662 node fruit-fly connectome, using the Kuramoto synchronization model. As this graph is less heterogeneous, lacking modular structure and exhibiting high topological dimension, we expect a difference from the previous results. Indeed, the synchronization transition is mean-field-like, and the width of the transition region is larger than in random graphs, but much smaller than as for the KKI-18 human connectome. This demonstrates the effect of modular structure and dimension on the dynamics, providing a basis for better understanding the complex critical dynamics of humans.